2018
DOI: 10.4315/0362-028x.jfp-17-161
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Food Safety Knowledge and Practices of Food Processors and Sellers Working in Food Facilities in Hanoi, Vietnam

Abstract: Consumption of fast food and street food is increasingly common among Vietnamese, particularly in large cities. The high daily demand for these convenient food services, together with a poor management system, has raised concerns about food hygiene and safety (FHS). This study aimed to examine the FHS knowledge and practices of food processors and sellers in food facilities in Hanoi, Vietnam, and to identify their associated factors. A cross-sectional study was conducted with 1,760 food processors and sellers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
1
9
1
Order By: Relevance
“…In Vietnam, the Ministry of Health reported that there were 677 incidents of food poisoning that affected more than 21,000 people over the period of 2011 to 2014 [ 5 ]. These numbers might just be an underestimation, since there are potentially many cases unrecognized, un-investigated or unreported in the communities [ 6 ]. The long-term effects of absorbing chemicals in contaminated food, which is generally believed in the community as possible links to getting cancers, have not been properly covered in Vietnam [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Vietnam, the Ministry of Health reported that there were 677 incidents of food poisoning that affected more than 21,000 people over the period of 2011 to 2014 [ 5 ]. These numbers might just be an underestimation, since there are potentially many cases unrecognized, un-investigated or unreported in the communities [ 6 ]. The long-term effects of absorbing chemicals in contaminated food, which is generally believed in the community as possible links to getting cancers, have not been properly covered in Vietnam [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the effectiveness of such efforts may be undermined by existing economic and developmental issues such as legislation, infrastructure, enforcement mechanisms, and people’s awareness, which occur in Vietnam and other low- and middle-income countries as well [ 9 ]. Moreover, the country has long possessed a culture where street food plays an important role, while the majority of foodborne disease outbreaks were reported at the food facilities instead of home settings [ 6 ]. Although the main responsibility of ensuring food safety may be that of food producers, manufacturers, and traders, it has been argued that consumers should also be proactive and take preventive cautions, adhering to food safety practices in order to protect themselves from the risks of foodborne illnesses [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Street food vendors were found to have a low level of food handling practices in Vietnam [ 17 ]. A lack of food hygiene and safety knowledge was reported for three domains, which includes standard requirements for food facilities, food poisoning prevention, and food processing procedures [ 18 ]. Notably, many foodborne illness cases are associated with home environments as a result of the improper handling and preparation of food among food caregivers [ 19 ].…”
Section: Introduction and Study Backgroundmentioning
confidence: 99%
“…Additionally, it is important to consider the vulnerable population including elderly, pregnant, and children who reside at home and are more susceptible to the detrimental effects of foodborne illness [ 19 ]. However, the majority of previous studies focused on food sellers [ 17 , 18 ]. In contrast, food safety at home, which is considered as the last line of foodborne disease prevention [ 19 ], has been neglected in Vietnam.…”
Section: Introduction and Study Backgroundmentioning
confidence: 99%
“…The level of food safety knowledge among market vendors is also an essential factor for implementing proper hygienic practices (Mahajan et al, 2014). In one study, it was shown that many Asian food peddlers were not adequately trained on the issue of public health management or food safety standards for avoiding the spread of foodborne illnesses (Minh, 2017; Ghatak and Chatterjee, 2018; Tran et al, 2018). Adding to Hong Kong’s high ambient temperatures and customer densities within markets, conditions favoring the growth, colonization and spread of food-borne pathogens on these cutting boards can be enhanced (Kotzekidou, 2016).…”
Section: Introductionmentioning
confidence: 99%